Purification, Characterization and Bioactivities of Polysaccharides Extracted from Safflower (Carthamus tinctorius L.) - Qiongqiong Wang; Shiqi Liu; Long Xu; Bin Du; Lijun Song (Molecules, 2023)
Polysaccharides are the main bioactive components in safflower. In this study, safflower polysaccharides (SPs) were extracted by ultrasonic assisted extraction, and four purified safflower polysaccharide fractions (named SSP1, SSP2, SSP3, and SSP4, respectively) were obtained. The physicochemical properties and in vitro physiological activities of the four fractions were investigated. The molecular weights (MW) of the SSPs were 38.03 kDa, 43.17 kDa, 54.49 kDa, and 76.92 kDa, respectively. Glucuronic acid, galactose acid, glucose, galactose, and arabinose were the main monosaccharides. The Fourier transform infrared spectroscopy (FT-IR) indicated that the polysaccharides had α- and β-glycosidic bonds. Nuclear magnetic resonance (NMR) analysis showed that SSP1 had 6 different types of glycosidic bonds, while SSP3 had 8 different types. SSP3 exhibited relatively higher ABTS+ scavenging activity, Fe+3-reduction activity, and antiproliferative activity. The results will offer a theoretical framework for the use of SPs in the industry of functional foods and medications.